Öğretmen görüşlerine göre lise yöneticilerinin yöneticilik beceri düzeylerinin incelenmesi - Avcı, Mürvet (My University, 2015)
ÖĞRETMEN GÖRÜŞLERİNE GÖRE LİSE YÖNETİCİLERİNİN YÖNETİCİLİK BECERİ DÜZEYLERİNİN İNCELENMESİ Bu araştırmanın amacı, ortaöğretim okul yöneticilerinin insanlarla iletişim kurma ve etkili biçimde çalışma, yeterli bir okul binası ve çevresi hazırlama, mesleğe hizmet, etkili bir örgüt yönetimi ve eğitim programının geliştirilmesi başlıkları altında sahip oldukları yeterliklerinin öğretmen görüşleri doğrultusunda belirlemektir. Bu amaç kapsamında resmi ortaöğretim okulu yöneticilerinin sahip oldukları yeterliklerinin öğretmen görüşleri doğrultusunda belirlenmesi ve bu görüşlerin öğretmenlerin görev yaptığı okul türlerine, branşlarına, cinsiyetlerine, kıdemlerine, mezun oldukları okul türüne, daha önceden yöneticilik deneyimlerinin olup olmadığına ve bulundukları okuldaki çalışma sürelerine göre farklılaşma durumu irdelenmiştir. Bu araştırma, İstanbul ilinde 2013-2014 eğitim öğretim yılında, Avrupa yakasından Sarıyer, Kağıthane, Başakşehir; Anadolu yakasından ise Sancaktepe ve Ataşehir ilçelerinde bulunan, Milli Eğitim Bakanlığı’na bağlı 15 resmi ortaöğretim okulunda gerçekleştirilmiştir. Lise yöneticilerinin yeterliklerini belirlemek amacıyla liselerde görevli öğretmenlerin görüşlerine başvurularak yapılmıştır. Araştırmada Ağaoğlu, E. (2012) tarafından geliştirilen ve geçerlik güvenirliği test edilmiş ‘‘Okul Yöneticilerinin Yeterlikleri Envanteri’’ ilgili okullardaki 576 öğretmene uygulanmıştır. Araştırmada nicel araştırma yöntemi kullanılmıştır, verilerin analizinde frekans, yüzde, aritmetik ortalama, betimsel istatistik yöntemleri, bağımsız grup t testi, tek yönlü varyans analizi (ANOVA) ve Tukey testi kullanılmıştır. Araştırma bulgularına göre; lise yöneticilerinin yeterliklerinin öğretmen görüşlerine göre hangi düzeyde olduğuna ilişkin yanıtların aritmetik ortalaması 3,40 çıkmış olup lise öğretmenlerinin yöneticilerinin yeterliklerine ilişkin algılarının “Kısmen Yeterli” olduğu görüşüne ulaşılmıştır. Okul yöneticilerinin yeterliklerine ilişkin algıların tüm alt boyutlardaki aritmetik ortalama değerleri birbirine yakındır. Bu alt boyutlardaki yeterlik alanları içerisinde sahip oldukları en yüksek seviyedeki yeterlik alanının “Yeterli Bir Okul Binası ve Çevresi Hazırlama” boyutundaki davranışlar olduğu görülmektedir. “Okul Türü” değişkenine göre öğretmenlerin okul yöneticilerinin yeterliklerine ilişkin algılarında anlamlı bir farklılık bulunduğu anlaşılmaktadır. Öğretmenlerin algıları arasındaki farklılığın “Meslek Lisesi” öğretmenleri ile “Anadolu Lisesi” ve “Anadolu İmam Hatip Lisesi” öğretmenleri arasında olduğu; “Anadolu Lisesi” ve “Anadolu İmam Hatip Lisesi” öğretmenlerinin, “Meslek Lisesi” öğretmenlerine oranla yöneticilerini daha yeterli buldukları görülmektedir. Öğretmenlerin okul yöneticilerinin yeterliklerine ilişkin algıları “Cinsiyet”, “Branş”, “Daha Önceden Yöneticilik Deneyimlerinin Olup Olmadığı”, “Bulundukları Okuldaki Çalışma Süreleri” değişkenlerine göre anlamlı bir farklılık ortaya koymamıştır. “Mezun Olunan Okul Türü” değişkenine göre öğretmenlerin yöneticilerinin yeterliklerine ilişkin görüşleri incelendiğinde “İnsanlarla İletişim Kurma ve Etkili Biçimde Çalışma” alt boyutu dışında anlamlı bir fark olmadığı görülmüştür. Bu alt boyut içerisindeki anlamlı farklılığın ise “Lisansüstü” mezunu öğretmenlerin “Önlisans” mezunu öğretmenlere oranla yöneticilerini daha yeterli buldukları yönünde farklılaşmaktadır.

HIGH SCHOOL TEACHERS’ OPINIONS ABOUT THE LEVELS OF ADMINISTRATIVE COMPETENCIES OF HIGH SCHOOL ADMINISTRATORS This study is intended to identify the secondary school administrators’ competencey levels in terms of communicating and working effectively with people, providing an adequate school building and environment, ministering to the profession, developing effective organization management and academic program based on the views of the teachers. In this framework, the competencies of the administrators of the public high schools have been identified based on the teachers’ views and the teachers’ views have been analyzed to find out if teachers’ views differed by the type of the schools they work in, branch, gender, seniority, the university degree, their previous experience as an administrator if any, and the term of employment in their current school. This research was conducted in Istanbul in the 2013-2014 academic year and it covered 15 public schools affiliated to the Ministry of Education from Sarıyer, Kağıthane and Başakşehir districts in the European side and from Sancaktepe and Ataşehir districts in the Anatolian side. The opinions of the high school teachers have been consulted to identify the high school administrators’ level of competence. “The Competencies of the School Administrators Inventory,” which was developed by Ağaoğlu, E. (2012), was given to 576 teachers in the above-mentioned schools. In this study, the quantitative research method was applied and the followings were used to analyze the data: frequency, percentage, arithmetical average, descriptive statistical techniques, independent group t test, one-way analysis of variance (ANOVA), and Tukey test. According to the research findings, the arithmetical average of the responses concerning the high school administrators’ level of competence in teachers’ view is 3,40 and it has been concluded that the high school teachers’ perception of the high school administrators’ level of competence is “Partially Adequate.” The arithmetical average values of the perceptions about the school administrators’ level of competence are close for each sub-dimension. It has been found out that the highest level of competence possessed by the school administrators among each sub-dimension is related to “Providing an Adequate School Building and Environment.” According to the “Gender” variable, there is no significant difference between male and female teachers’ view about the competence level of the school administrators. According to the “School Type” variable, it is evident that there is significant difference between the teachers’ perception of the school administrators’ level of competence. It has been found out that the perceptions of the “Vocational High School” teachers are different from those of the “Anatolian High School” and “Anatolian Religious Vocational High School” teachers. Accordingly, the teachers from the “Anatolian High Schools” and “Anatolian Religious Vocational High Schools” see their administrators more competent when compared to the teachers from the “Vocational High Schools.” No significant difference has been concluded about teachers’ views about the high school administrators’ level of competence by the “Branch,” “Previous Experience as an Administrator,” and the “Term of Employment Year in the Current School” variables. The teachers’ views about the school administrators’ level of competence differed in six sub-dimensions by the “Professional Seniority” variable. In general, the teachers who have been working for “6-10 years” found their administrators more competent than those who have been working for “0-5 years;” and the teachers who have been working for “16 and more years” perceived their administrators more competent than those who have been working for “6-10 years.” When the teachers’ views about the competence level of their administrators are reviewed by the “type of the university degree” variable, no significant difference has been found out except for the “Communicating and Effectively Working with People” sub-dimension. For this sub-dimension, it has been found out that the teachers with a “Postgraduate” degree perceived their administrators as more competent than those with an “Associate” degree.
Keywords: Okul müdürleri; Okul yöneticileri; Okul yönetimi ve örgütü